Strategy to Improve Training Quality in PPSDM Migas: Approach to Educational Aspects, Facilities, and Services - Yusran Hedar; Mario Emilzoli; Ai Pemi Priandani; Mohd Lokman Abdullah (CV. Media Inti Teknologi, 2025)
Background: Improving the quality of training delivery in the oil and gas sector is a strategic necessity in the face of global energy transition and technological disruption. As a technical training institution under the Ministry of Energy and Mineral Resources, PPSDM Migas must ensure that its training programs remain relevant, effective, and responsive to participants’ needs.Aims: This research aims to develop a strategic framework for enhancing training quality at PPSDM Migas through evaluative analysis across three core aspects: educational content, facilities, and services.Methods: An evaluative quantitative research design with qualitative support was employed, involving 1,539 training participants through total sampling. Data were collected using structured questionnaires assessed for validity through pilot testing. Analysis included descriptive statistics, gap analysis, SWOT mapping, and the PDCA model to formulate improvement strategies.Results: The findings revealed performance gaps in all aspects, particularly in facilities (gap = -3.35). The gap analysis and participant feedback identified specific weaknesses such as poor ICT infrastructure and lack of interactivity. SWOT analysis and PDCA were used to recommend targeted strategies including ICT upgrades, training material redesign, and service digitization.Conclusion: The resulting strategy framework supports continuous training improvement and reinforces PPSDM Migas's role as a future-ready institution. The research contributes to the literature on evaluation-based quality development and opens avenues for further research on adaptive training innovations in technical education.